Relative clauses in a spoken corpus of European Portuguese: identifying the factors determining their variation - Elisabeth, Aßmann; Rinke, Esther (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
This paper investigates a range of factors determining variation in European Portuguese (EP) relative clauses on the basis of a corpus study. From a more general perspective, we aim at empirically confirming or disconfirming generalizations formulated on the basis of introspection or standard language grammars. In addition, we seek to identify preferences within the “envelope of variation” in actual language use. We will focus on three variable aspects in EP relative clauses: i) the choice of the relativizer, ii) non-canonical relative clauses (preposition chopping and resumption), and iii) subject-object asymmetries and related information structural aspects. The results confirm that que is the default relativizer in spoken EP, and that animacy determines the choice of the relativizer in free relative clauses and headed relative clauses introduced by a preposition. Resumption is attested in various types of relative clauses and seems to be favoured in headed indirect object relative clauses. The relevance of other factors such as indefiniteness or presentational matrix verbs, however, cannot be confirmed. Chopping occurs in restrictive as well as non-restrictive relative clauses and with different prepositions, e.g. temporal prepositions, grammaticalized (“verbal”) prepositions but also in oblique and indirect object relative clauses. Finally, the corpus data provide evidence for a subject-object asymmetry that relates to information structural aspects.